"What the Papers Say": Archives in the English-Language Canadian Public Press, 1989-1994 - Craig, Barbara Lazenby (Archivaria, 1995)
A search of the English-language Canadian press from 1989 to 1994 located 365 reports featuring archives. These stories included specific acquisitions, the preservation activities of certain institutions, and more general comments on the role of the archivist as an intermediary between documents and users. While some conclusions do not suit the knowledgeable archivist, the sense of archives in the press, however untutored, has some surprising features. Stereotypes can be found but often they are eclipsed in number and importance, by larger ideas about archives and their role in politics, cultural memory, and personal life. Archival documents are portrayed by the public press as objects which carry much more than data into the information age. Archivists may find awareness of press reports to be useful in advocacy and in developing programmes that appeal to diverse sectors of the public. RÉSUMÉ Une recherche dans la presse canadienne-anglaise entre 1989 et 1994 a permis de découvrir que les institutions d'archives y figurent à 365 reprises. Ces articles concernent des acquisitions particulières, les activités de conservation de certaines institutions et des commentaires d'ordre général sur le rôle de l'archiviste comme intermédiaire entre les documents et les utilisateurs. Bien que certaines conclusions ne conviennent pas à l'archiviste professionnel, le rôle des archives, bien que superficiellement exprimé, y est parfois décrit de manière étonnante. Des stéréotypes peuvent s'y dissimuler, mais ceux-ci sont souvent éclipsés en nombre et en importance par des considérations d'ordre général à propos des institutions d'archives et leur rôle en politique, pour la mémoire culturelle ou la vie personnelle. Les documents archivistiques sont décrits dans la presse comme des objets véhiculant une signification supérieure à leur valeur pour la recherche à l'âge de l'information. Les archivistes pourront trouver utile cette sensibilisation de la presse à ce sujet pour la défense et le développement des programmes qui touchent différentes couches de la population.